A Systematic Functional Linguistics Writing Approach in an Online Mandarin as a Foreign Language Course - Kuan, Wee Ling (Research, Industrial Linkages, Community & Alumni Network Universiti Teknologi MARA Perak Branc, 2021)
Guided writing instruction is a widely used scaffolding strategy. Nevertheless, most of the Mandarin as a Foreign Language (MFL) students have struggled with their guided writing essays. All the information in the guided writing essay is presented in the form of keywords. Initially, the students were still unsure what to write about using the keywords provided and they were unsure where to begin writing, especially in an online MFL course. This study aims to investigate the adapted Systemic Functional Linguistics (SFL) writing approach to guided writing instruction in an online MFL communicative course. Whiteboard.fi is used as an online tool to guide the students throughout the writing process. The SFL writing approach includes three categories of language aspects relevant to meaning-making that are organised step by step: ideational, interpersonal, and textual. A single group experimental design was used for the pre-test and post-test. This study includes twenty MFL students from a UNIMAS intermediate level MFL classroom in the first semester of the 2020/2021 academic year. The results of the pre-test and post-test have been analysed and three writing samples have been chosen for in-depth analysis. The quantitative results showed that the experimental group showed a significant and positive effect on their writing performance. The qualitative results revealed that there was a wide range of sentence patterns, grammar, and logical sequence of ideas in writing in the post-test when compared to the pre-test. The adapted SFL writing approach and the integration of Whiteboard.fi as an online tool are effective in improving students' writing competence and scaffolding their generation of writing ideas in an online MFL communicative course.